O estatuto da alegoria e da interpretação alegórica em Platão - Orlandi, Juliano (2015)
The theme of this thesis is the use of allegories and allegorical interpretation in the works of Plato. It arises from the verification of a paradox between the occurrences of this rhetorical or literary device and the negative comments that the philosopher addresses sometimes to them. In certain passages of his dialogues, such as the beginning of the Book VII of The Republic (514a to 517a), Plato presents metaphorical narratives which add themselves, without any restriction on his part, with the argumentative development of his ideas. In other parts, however, as at the prologue to the Phaedrus (229c-230a), he expresses unfavorable opinions about the allegories and allegorical interpretation. In this sense, the philosopher seems to reject a discursive device that, paradoxically, he usually employs. My goal is therefore examine comparatively the allegorical passages of the corpus platonicum to reveal its constituent structure and the possible variations to which they are submitted. What I hope, in fact, is to find the theoretical notions that allow dissolve the paradox and restore the internal coherence of platonic thought on the issue of allegories.